Isoniazid induced hepatotoxicity and its amelioration with ethanolic extract of stem bark of Berberis lycium Royale in mice - Rafiq, Saima; Ajmal, Khalida; Afzal, Ayesha (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To study the hepatoprotective effect of Ethanolic extract of Stem Bark of Berberis lycium Royale in isoniazid (INH) induced hepatotoxicity in mice model. Methods: The study design was lab based randomized controlled in-vivo study in mice conducted from 9th April 2014 till 9th May 2014 at animal house of National Institute of Health, Islamabad. Group A was on normal diet and water and hepatotoxicity was produced by giving isoniazid (50mg/kg BW) in mice of Group B. Group C and D were given isoniazid (INH) plus low dose and high dose of Ethanolic extract of stem bark of Berberis Lycium Royle respectively. Results: INH induced hepatotoxicity was depicted by elevated serum LFT’s, hepatocytic ballooning, severe steatosis and inflammation. Mice getting concurrent treatment of INH, low and high dose of Ethanolic extract of Berberis Lycium Royle showed decreased serum levels of biomarkers and their liver sections manifested improved histological picture but more significant reduction in toxic effects were observed in animals receiving high dose. Conclusions: High dose of Ethanolic extract of stem bark of Berberis lycium Royale showed more marked hepatoprotective activity as compare to low doses. The hepatotoxicity of INH can be reduced by concurrent use of INH with ethanolic extracts of Berberis Lycium Royle.